Checklist of marine mammal parasites in New Zealand and Australian waters. Issue 6 (November 2019) - Lehnert, K.; Poulin, R.; Presswell, B.
Abstract: Marine mammals are long-lived top predators with vagile lifestyles, which often inhabit remote environments. This is especially relevant in the oceanic waters around New Zealand and Australia where cetaceans and pinnipeds are considered as vulnerable and often endangered due to anthropogenic impacts on their habitat. Parasitism is ubiquitous in wildlife, and prevalence of parasitic infections as well as emerging diseases can be valuable bioindicators of the ecology and health of marine mammals. Collecting information about parasite diversity in marine mammals will provide a crucial baseline for assessing their impact on host and ecosystem ecology. New studies on marine mammals in New Zealand and Australian waters have recently added to our knowledge of parasite prevalence, life cycles and taxonomic relationships in the Australasian region, and justify a first host–parasite checklist encompassing all available data. The present checklist comprises 36 species of marine mammals, and 114 species of parasites (helminths, arthropods and protozoans). Mammal species occurring in New Zealand and Australian waters but not included in the checklist represent gaps in our knowledge. The checklist thus serves both as a guide for what information is lacking, as well as a practical resource for scientists working on the ecology and conservation of marine mammals.